Predictors of Fatal Outcomes in Cerebral Aneurysm Rupture - Anastasiia Revurko; Yuliia Solodovnikova (Galician Medical Journal)
Introduction. Aneurysmal subarachnoid hemorrhage (aSAH) is associated with high mortality and disability. Previous studies have reported a range of factors influencing in-hospital mortality after aSAH, sometimes with conflicting findings. This study aimed to identify predictors of fatal outcomes in ruptured cerebral aneurysms (CAs).